Plasma Cell Alloantigen 1 and IL-10 Secretion Define Two Distinct Peritoneal B1a B Cell Subsets With Opposite Functions, PC1high Cells Being Protective and PC1low Cells Harmful for the Growing Fetus - Schumacher, Anne; Ehrentraut, Stefanie; Scharm, Markus; Wang, Hongsheng; Hartig, Roland; Morse, Herbert C.; Zenclussen, Ana Claudia (Frontiers in Immunology, 2018)
B cells possess a variety of immuno regulatory functions. However, research about their participation in tolerance induction towards the fetus is just emerging. Accumulating evidence supports the idea that B cells can play seemingly conflicting roles during pregnancy, either protecting or harming the fetus. Previous findings indicated the presence of two different peritoneal B cell subsets, defined by the expression of the plasma cell alloantigen 1 (PC1) and with distinct immune modulatory functions. Here, we aimed to study the participation of these two B cell subsets, on pregnancy outcome in a murine model of disturbed fetal tolerance. The frequencies and cell numbers of peritoneal and splenic CD19+IL-10+ and CD19+CD5+IL-10+PC1+ cells were assessed in virgin as well as normal pregnant and abortion-prone females during the course of gestation. Peritoneal PC1low or PC1high B1a B cells were sorted, analyzed for their ability to secrete IL-10 and adoptively transferred into normal pregnant or abortion-prone females. On gestation day (gd)12, the abortion rate as well as the frequencies and cell numbers of regulatory T cells, TH1 and TH17 cells were determined in spleens and decidua. In addition, mRNA expression of IL-10, TGF-β, IFN-γ and TNF-α was analyzed in decidual tissue. Peritoneal CD19+IL-10+ and CD19+CD5+IL-10+PC1+ frequencies fluctuated during the progression of normal pregnancies while no significant changes were observed in spleen. Abortion-prone females showed significantly reduced frequencies of both B cell populations and exhibited an altered peritoneal PC1high/PC1low ratio at gd10. Adoptive transfers of PC1low B1a B cells into normal pregnant females increased the abortion rate in association with a reduced splenic Treg/TH17 ratio. By contrast, the transfer of PC1high B1a B cells into abortion-prone females significantly diminished the fetal rejection rate and significantly reduced the numbers of splenic TH17 cells. Our results suggest that the peritoneum harbors two distinct B1a B cell subsets that can be distinguished by their PC1 expression. Whereas PC1high B1a B cells seem to support fetal survival, PC1low cells B1a B cells may compromise fetal well-being.